Dalil Hukum Hak dan Kewajiban Suami Istri - Nur Suci Alawiyah; Mhd. Amar Adly; Heri Firmansyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Establishing the rights and responsibilities of each family member is a strategy to build and maintain harmony between husband and wife. Household harmony is difficult to achieve without being balanced with knowledge and awareness in fulfilling obligations to uphold the rights of one’s partner. Inequality will inevitably arise if there is an imbalance where rights are prioritized or expanded over obligations, or vice versa. This type of research is referred to as Library Research, utilizing a content analysis approach to process data descriptively and analytically while still relying on qualitative data. This study will discuss the legal foundations of the rights and responsibilities of husband and wife, including texts from the Quran and Hadith. Islamic law, as agreed upon, derives its sources from the Quran, Sunnah, Ijma', and Qiyas.